1965
DOI: 10.1063/1.1704268
|View full text |Cite
|
Sign up to set email alerts
|

Invariant Approach to the Geometry of Spaces in General Relativity

Abstract: A procedure is described for obtaining a complete, invariant classification of the local, analytic geometries and matter fields in general relativity by a finite number of algebraic steps. The approach is based on an extension of the classification scheme to include differential invariants of all orders and to provide maximally determined standard frames of vectors at each point. It is further shown that the resultant invariant functions can be replaced, in a finite number of algebraic steps, by special invari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 3 publications
0
75
0
1
Order By: Relevance
“…This result, as suggested by Brans [3] and further developed by Karlhede [4], may be used to provide a coordinate independent characterization of gravitational fields in general relativity. Based on this idea, Karlhede et al [5] have investigated the simplest scalar invariant, I ≡ R µνρσ;δ R µνρσ;δ , constructed from the first covariant derivative of the curvature tensor, and found that the behavior of this locally measurable scalar reveals the effect of passage through the event horizon of the Schwarzschild spacetime -a static solution to the vacuum Einstein equation, R µν = 0.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This result, as suggested by Brans [3] and further developed by Karlhede [4], may be used to provide a coordinate independent characterization of gravitational fields in general relativity. Based on this idea, Karlhede et al [5] have investigated the simplest scalar invariant, I ≡ R µνρσ;δ R µνρσ;δ , constructed from the first covariant derivative of the curvature tensor, and found that the behavior of this locally measurable scalar reveals the effect of passage through the event horizon of the Schwarzschild spacetime -a static solution to the vacuum Einstein equation, R µν = 0.…”
Section: Introductionmentioning
confidence: 93%
“…Thus the local geometry of STE spacetimes with I B = 0 is of considerable interest. In general, for the class of 4-dimensional STE spacetimes, we find that the vanishing of I B implies that (3) Σ is locally foliated by 2-dimensional surfaces, (2) S, of constant curvature. From the resulting structure of (3) Σ, we show that any nonflat static solution to R µν = Λg µν must be either Kottler-type or Nariai-type [subsection 3.4] if I B = 0.…”
Section: Introductionmentioning
confidence: 99%
“…Two examples of such work are given by references [2,4]. We also note that geometrical structures, in Cartan's sense, induced on null hypersurfaces in n-dimensional space-times have been investigated in reference [3].…”
Section: The Local Version Of This Definition Ismentioning
confidence: 99%
“…(However it is in practice often convenient to use the twice contracted Bianchi identities since they give simple relations, but they may of course be derived from the other equations). Hence the system (13,14) is the complete system. It is a set of first order ordinary differential equations, where the independent variable is ρ, and algebraic constraints.…”
Section: B Symmetry Groupmentioning
confidence: 99%
“…To find the solutions we use a method for construction of solutions to Einstein's equations, [13][14][15][16], based on the invariant classification scheme by Cartan and Karlhede [17,18]. The method is shortly described in section II.…”
Section: Introductionmentioning
confidence: 99%